Підвищення якості електричної енергії в розподільних мережах за рахунок удосконалення перетворючів енергії - Лисиченко, Роман Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.14.02 – електричні станції, мережі і системи. – Харківський національний технічний університет сільського господарства імені Петра Василенка, Харків, 2021. Дисертація присвячена вирішенню наукової задачі підвищення якості електричної енергії шляхом зменшення гармонійних складових від перетворювачів енергії. Задача, пов'язана з недостатньою ефективністю існуючих сьогодні методів забезпечення зменшення рівня гармонійних складових від нелінійних споживачів до яких відносяться інвертори управління асинхронними двигунами змінного струму. Проведений в роботі аналіз виявив необхідність розробки методів по підвищенню якості електричної енергії в розподільних мережах. Система керуючий інвертор і двигун є джерелом гармонічних складових і основним джерелом погіршення якості електричної енергії. В роботі запропоновано метод керування спектральними характеристиками інверторів із цільовою функцією якості електричної енергії, що дозволило розробити засади для створення інверторів зі зменшеними показниками спотворення форми напруги і струму. Запропоновано технічні рішення і обґрунтована можливість використання методів спектрального збудження силових перетворювачів енергії, що забезпечують зниження рівнів гармонійних складових електричної енергії, що створюються як нелінійним навантаженням, так і мережею живлення. У порівнянні з пасивними фільтрами і активними фільтрами, методи спектрального збудження силових перетворювачів енергії не потребують спеціальної настройки під параметри конкретної мережі і відрізняються надійністю. Розроблено апаратно інформаційну систему, яка дозволяє зменшити вплив від гармонійних складових на споживачів і систему електропостачання при різних режимах роботи частотного регулювання електричних двигунів. Результати експериментальних досліджень розробленої системи показали її відповідність технічним вимогам та можливість отримання діагностичної інформації при різних режимах роботи електродвигунів. Елементи конструкції та принцип дії розробленої системи для частотного регулювання захищені патентами України.

Dissertation for the degree of candidate of technical sciences in specialty 05.14.02 – power plants, networks and systems. – Kharkiv National Technical University of Agriculture named after Petro Vasilenko, Kharkiv, 2021. The dissertation is devoted to the decision of a scientific problem of increase of quality of electric energy by reduction of harmonic components from energy converters. Thus, there is an urgent scientific problem associated with the lack of efficiency of existing methods to reduce the level of harmonic components from nonlinear consumers, which include inverters for controlling induction AC motors. The analysis revealed the need to develop methods to improve the quality of electricity in distribution networks. The widest distribution of various devices and equipment with induction motors, which are controlled by inverters. The control system of the inverter and the motor is a source of harmonic components and the main source of deterioration of electric energy. The solution of the specified problem at the expense of decrease in harmonic components by a method of management of spectral characteristics of inverters is offered. The following main scientific results were obtained: – for the first time the method of control of spectral characteristics of inverters with target function of quality of electric energy is offered that allowed to develop bases for creation of inverters with the reduced indicators of distortion of a form of tension and current; – further developed the theory of the origin of harmonic components in electric current from power energy converters, which, in contrast to the known, allowed to determine the spectral methods of excitation as the most balanced from an economic and technical point of view; – the model of spectral excitation of power energy converters was further developed, which allows to obtain mathematically substantiated spectral-energy dependences in the external network; – technical solutions are offered and the possibility of using methods of spectral excitation of power energy converters is substantiated, which provide reduction of levels of harmonic components of electric energy, created both by nonlinear loading and power supply network. In comparison with passive filters and dynamic filters, methods of spectral excitation of power converters of energy do not demand special adjustment under parameters of a concrete network and differ in reliability; – algorithms for determining the parameters of spectral excitation of power energy converters and methods of modeling their operation in the Matlab environment are developed, which differ taking into account the parameters of a particular network, ensuring their construction and application at existing and projected power facilities. Of practical importance for instrument making are approaches and recommendations for the construction of control systems for the spectral characteristics of inverters, which allows you to create equipment with reduced impact on the quality of electricity. The practical problem of development of methods of control of spectral characteristics of inverters of asynchronous electric motors with the reduced influence on qualitative indicators of electric energy is solved. On the basis of the offered approaches and methods the information technology of reception of commands of spectral excitation of power converters of energy with use of mathematical methods is developed. A hardware information system has been developed, which allows to reduce the impact of harmonic components on consumers and the power supply system at different modes of operation of frequency control of electric motors. The results of experimental studies of the developed system showed its compliance with technical requirements and the ability to obtain diagnostic information in different modes of operation of electric motors. Elements of construction and the principle of operation of the developed system for frequency control are protected by patents of Ukraine (Pat. № 101521, Pat. 113090). The results of the work are implemented in the educational process of the Department of Power Supply and Energy Management of Petro Vasylenko Kharkiv National Technical University of Agriculture when teaching the course "Technologies, problems and prospects of industry development".
Improving the quality of electrical energy in distribution networks by improving energy converters
Keywords: автореферат дисертації; розподільна мережа; якість електропостачання; гармонічна складова; асинхронний електричний двигун; інвертор; нелінійний споживач; distribution network; quality of power supply; harmonic component; asynchronous electric motor; inverter; non-linear consumer; 621.316.051.3:621.314